Tailoring Ferromagnetic Resonance Properties of Cobalt Nanowires: Effects of Shape and Magnetocrystalline Anisotropies - Escrig-Murua, J; Saavedra-Díaz, E (Royal Society of Chemistry, 2024)
In this study, we investigate the influence of shape and magnetocrystalline anisotropies on the magnetic dynamic susceptibility of individual cobalt nanowires (Co-NWs) through micromagnetic simulations. The simulations encompassed a range of nanowire diameters from 10 to 150 nm and lengths from 50 nm to 1 μm, considering three magnetocrystalline anisotropy scenarios: no anisotropy, easy-plane anisotropy, and easy-axis anisotropy. The results reveal that shape anisotropy leads to ground states characterized as flower, twisted flower, or vortex configurations, while the prevalence of flower or vortex states depends on whether easy-axis or easy-plane magnetocrystalline anisotropy is present, respectively. The interplay between shape and magnetocrystalline anisotropies yields diverse effects in the ferromagnetic resonance response, contingent upon the nanowire s ground magnetic state. For Co-NWs with flower and twisted flower states, the edge-mode frequency can be modulated predominantly by varying the nanowire diameter, while the fundamental-mode frequency is influenced by the nanowire s length. In contrast, Co-NWs with a vortex state exhibit azimuthal mode, with their number and frequencies primarily dependent on the nanowire diameter, while gyrotropic modes are affected by the nanowire s length. Furthermore, nanowires featuring uniaxial magnetocrystalline anisotropy (MCA) exhibit higher resonant frequencies compared to those without MCA. The insights gained from this investigation offer valuable guidance for tailoring cobalt nanowires with specific ferromagnetic resonance properties, facilitating their utilization in various applications. © 2024 The Royal Society of Chemistry.